Racial and Ethnic Differences in Infant Feeding Practices and Growth Trajectories Among Low-Income Households. (14th June 2022) - Frazier, Christina; Dharod, Jigna; Labban, Jeffrey; Hernandez, Marlen; Ramos-Casillo, Isa; Raynor, Nichole
Abstract: Objectives: (1) To examine duration and intensity of breastfeeding, age of introduction to solids/other liquids, and complementary feeding choices among racial/ethnic minority infants living in low-income households. (2) To determine the association between feeding choices and model growth trajectory from early to late infancy in the study population. Methods: Mother-infant dyads were recruited from a pediatric clinic mainly serving low-income and/or Medicaid-recipient families. Mothers were interviewed in English or Spanish to collect sociodemographic, food security status, and feeding practices when the infant was 2, 4, 6, 9, and 12 months of age (n = 249). From 6-months onwards, 24-hour feeding recalls were conducted to estimate daily nutrient intake. Infant height and weight were retrieved from the electronic medical record to estimate growth trajectories from early to late infancy. Results: By race/ethnicity, the majority of the participants were African American (46%) or Hispanic (35%). The prevalence of low to very low food insecurity was 10%. Exclusive breastfeeding was not common among dyads at 2 (26%), 4 (17%), and 6 months (4%). Partial breastfeeding was significantly higher among Hispanic mothers (P < .05). For instance, at 4 months 72% of Hispanic mothers partially breastfed compared to 34% African American and 31% of non-Hispanic White mothers ( p  < .001). Early introduction to solids/other liquids was more common within African American dyads ( p  < .05). Preliminary growth trajectory modeling indicated some racial/ethnic differences, especially the weight of Hispanic infants was marginally higher compared to non-Hispanic white infants ( p  = .072) in late infancy. Conclusions: Significant differences in infant feeding practices, including breastfeeding and introduction to solids/liquids, exist by race/ethnicity. Examination of these differences in feeding practices will be critical to understanding how they affect growth trajectory from early to late infancy. Funding Sources: National Institute of Health NICHD.